Letermovir use for cytomegalovirus prophylaxis following lung transplantation: A single-center review - Alyssa K. Mezochow, MD, MSc; Kevin D. He, MD; Kathryn Whitaker, MD; Emily Blumberg, MD; Maria M. Crespo, MD; Andrew Courtwright, MD, PhD (JHLT Open)
Background: Cytomegalovirus (CMV) remains a major cause of infection following solid organ transplant and valganciclovir prophylaxis is the standard of care. However, valganciclovir-associated myelosuppression limits its tolerability and can require dose reduction in immunosuppression, particularly cell cycle inhibitors, or changes in antimicrobial prophylaxis. Letermovir, a viral terminase inhibitor, is approved by the FDA for use as CMV prophylaxis in kidney transplant recipients; data on its use in lung transplant recipients (LTRs) are limited. Methods: We performed a single-center retrospective cohort study of LTRs prescribed letermovir for prophylaxis between January 1, 2018 and September 1, 2023. Results: Over the study period, 88 LTRs were prescribed letermovir with most (93%) switching due to myelosuppression while on valganciclovir. Of those prescribed letermovir, 67 (76%) actually started letermovir, with the primary barrier being insufficient insurance coverage or high copay cost. Among LTRs who started letermovir due to myelosuppression, 90% had improvement in their leukopenia or neutropenia, with a significant increase in white blood cell count 1 month after switching therapy (p < 0.0001). Additionally, 46% of those who were not receiving a cell cycle inhibitor previously were able to restart this after switching to letermovir. CMV was detected in 14 LTRs following letermovir switch, with 2 discontinuing letermovir due to breakthrough CMV. Conclusions: Our findings support the use of letermovir for CMV prophylaxis in LTRs with possible benefits over valganciclovir, although a direct comparison is needed.